Estrogen receptor signaling and the PI3K/akt pathway are involved in betulinic acid-induced eNOS activation - Hohmann, Nicolas; Xia, Ning; Steinkamp-Fenske, Katja; Förstermann, Ulrich; Li, Huige (Molecules, 2016)
Betulinic acid (BA) is a naturally occurring pentacyclic triterpenoid with anti-inflammatory, antiviral and anti-cancer properties. Beneficial cardiovascular effects such as increased nitric oxide (NO) production through enhancement of endothelial NO synthase (eNOS) activity and upregulation of eNOS expression have been demonstrated for this compound. In the present study, immortalized human EA.hy 926 endothelial cells were incubated for up to 1 h with 1-100 µM BA and with the phosphatidylinositol-3-kinase (PI3K) inhibitors LY294002 and wortmannin, or the estrogen receptor (ER) antagonist ICI 182,780. Phosphorylation status of eNOS and total eNOS protein were analyzed by Western blotting using a serine 1177 phosphosite-specific antibody. Bioactive NO production was assessed by determination of cGMP content in rat lung fibroblasts (RFL-6) reporter cells. Short-term incubation of EA.hy 926 cells with BA resulted in eNOS phosphorylation at the serine 1177 residue in a concentration- and time-dependent manner with a half-maximal effective concentration of 0.57 µM. This was associated with an enhanced production of NO. BA-induced eNOS phosphorylation and NO production was completely blocked by pretreatment with ICI 182,780, and was attenuated by pretreatment with the PI3K inhibitors wortmannin and LY294002. These results indicate that fast non-genomic effects of ER with downstream signaling through the PI3K/Akt pathway and consecutive eNOS phosphorylation at serine 1177 are involved in BA-induced eNOS activation.
Gesehen am 19.05.2020